(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
The study was applied to offshoots of date palms Barhi cv. tissue culture growing in one of the private orchards, The experiment included a study of the effect of two factors, the first factor as a soil improver (without adding improvers, an organic improver in which decomposing sheep waste was used by adding it to the soil, an industrial improver that treats salinity, Super soil ). As for the second factor, the quality of irrigation water, which included (irrigation water with low salinity, which is river water (4-5 dsm-1 , Control treatment), irrigation water with salinity ( 8 dsm-1 ), and irrigation water with salinity (15 ds m-1 ). The results of the study showed the effect of soil improvers and the quality of irrigation water on the anatomical characteristics of the roots of date palm offshoots of the Barhi cv, as the Super soil treatment was significantly superior to the organic fertilizer treatment and the Control treatment, and the highest mean thickness of the epidermis, cortex, endodermis, pericycle, diameter of vascular bundle, diameter of phloem and xylem reached (32.86, 860.14, 27.67, 24.33, 1356.67, 46.33 and 127.52µm) respectively, while the treatment without the addition of improvers (Contol) recorded the lowest mean for the same characteristics .The quality of irrigation water also had a significant effect on the anatomical characteristics of the roots, as it excelled with It low salinity irrigation water, which is the river water (5-4 dsm-1 ) significant and recorded the highest mean of the thickness of the epidermis, cortex, endodermis, pericycle, diameter vascular bundles, and diameter of phloem and xylem were (33.81, 863.57, 28.00, 23.67, 1360.00, 46.67 and 127.17 µm), respectively. While the treatment of irrigation water with salinity (15 dsm-1 ) recorded the lowest mean for the same characteristics. The interaction between the factor of improvers (Super soil ) and the factor of quality of irrigation water (4-5 dsm-1 ) recorded the highest mean for all characteristics, while the interaction between treatment without adding improvers (Control treatment ) and the salinity of irrigation water (15 dsm-1 ) was recorded the lowest means for all studied anatomical features